Debt Sustainability in the Euro Area When Interest Rates Are Low or Negative - Hans-Jörg Naumer (Wirtschaftsdienst)
Abstract Who is going to pay? That question is heard regularly in connection with corona-related fiscal packages. Quite rightly. Governments have adopted huge packages to stabilise their economies. While there is no shortage of suggestions of how the new public expenditure and old debt is to be funded, many people seem to be overlooking the fact that the current low or negative interest rate environment is already making a major contribution to debt reduction.